THU0269 Liposomal Local Therapy as Treatment of Sicca Symptoms in Patients with Primary SjöGren´s Syndrome. (23rd January 2014) - Hofauer, B.; Bas, M.; Mansour, N.; Knopf, A.
Abstract : Background: The primary Sjögren´s Syndrome (pSS) represents the most common rheumatologic disease in the head and neck area. Due to various nonspecific symptoms many different medical specialities get involved in diagnostic and therapeutic regimes of patients with pSS. Therefore a broad awareness of symptoms and therapeutic options is important. Effective management of Xerostomia, Keratoconjunctivis sicca (KCS) and Rhinitis sicca (RS) is essential in every patient to alleviate symptoms and prevent local complications. Various substitutes with different ingredients are available for topical and symptomatic therapy, but there are no generally accepted treatment suggestions due to the lack of studies proving effective relief of symptoms. Objectives: Is topic therapy with liposomal agents suitable for symptomatic treatment of sicca symptoms in pSS? Methods: Between October 2007 and August 2012 pSS was diagnosed in 73 patients according to the American European Consensus Group (AECG) criteria. Before and after a 2-month-period of treatment with liposomal agents for oral, nasal and ocular complaints (LipoSaliva®, LipoNasal® und Tears Again®) AECG-criteria and subjective symptoms expressed via visual analogue scales were evaluated. Results: Xerostomia (92%), KCS (92%) and recurrent salivary gland swelling (40%) were the leading clinical symptoms. Mean salivary flow rate was 1, 89g (Saxon-Test), mean lacrimal flow 12, 7mm (Schirmer-I-Test). SS-A/-B antibodies could be detected in 47/29% of cases. An average histologic focus score of 3 could be seen (Chisholm and Mason). Extraglandular manifestations were observed in 17%, severe local complications due to ineffective treatment of sicca symptoms were diagnosed in 71%, respectively. Liposomal local therapy caused a significant reduction of Xerostomia (p=0, 0001), KCS (p=0, 004) and RS (p=0, 004). Conclusions: Local therapy with liposomal agents is effective in the symptomatic treatment of Xerostomia, KCS and RS in patients with pSS. Disclosure of Interest: None Declared